ANALISIS PENGARUH INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA DENGAN METODE FINAL PREDICTION ERROR - Dwi Hartini; Yuni Prihadi Utomo (Muhammadiyah University Press, 2004)
The purpose of the research is to know whether inflation influences economic growth or economic growth influence inflation and to know the final prediction error of long - term equilibrium relationship between inflation and economic growth.The hypothesis presented in this research is that inflation has negative influence on economic growth and economic growth has negative influence on inflation. It is assumed that the final prediction error of long - term equilibrium relationship between inflation and economic growth has negative influence, and the final prediction error of equilibrium relationship between economic growth and inflation has negative influence.The method used in this research is causality analysis of Final Prediction Error (FPE) by using time series data of 1973 through 2002 taken from the Body of Statistic Center (BPS).It is conducted stationerity and causality test of FPE in this research. This research shows that there is one direction causality in which economic growth influences inflation.